Pendekatan Matematika Realistik Untuk Meningkatkan Hasil Belajar Siswa Kelas I Pada Operasi Hitung - Yusmaniar Yusmaniar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2017)
Teacher in mathematics learning process of 1st grade at SDN 21 Batang Anai Kabupaten Padang Pariaman used to implement expository method. It caused the learning achievement of students become low. This study is a classroom action research with two cycles that aimed to improve students’ learning achievement by implementing realistic mathematics education. Mean of students’ learning achievement score in cycle I is 77.2 and 88.2 for cycle II. Hence, realistic mathematics education can improve students’ learning achievement.